STRATEGI ORANG TUA DALAM MEMBATASI PENGGUNAAN GADGET DAN MENINGKATKAN MOTIVASI MEMBACA ANAK SDIT AL HUDA - Nofrianti, Wita; Kurniawan, Wakib; Kurniawan, Supriyatmoko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of digital technology has increased the use of gadgets among elementary school children, including students at SDIT Al Huda. Excessive and uncontrolled gadget use can reduce children’s reading motivation, learning concentration, and interest in literacy activities. Parents play an important role in supervising gadget use and encouraging positive learning habits, especially reading activities. This study aims to describe the strategies used by parents to limit gadget use and improve children’s reading motivation at SDIT Al Huda. This research employed a qualitative approach with a descriptive research design. The subjects of this study consisted of parents, teachers, and students at SDIT Al Huda. Data were collected through observation, interviews, and documentation. The findings revealed that parents applied several strategies, including limiting gadget usage time, supervising children while using gadgets, implementing religious-based rules, providing positive activities, and becoming role models for children. Parents also increased reading motivation through reading habits, reading together, providing literacy facilities, and giving rewards. The study further found that integrating religious activities such as Qur’an recitation and murojaah before gadget use was an effective strategy to reduce gadget dependency and develop reading habits among children. Therefore, parental involvement plays a significant role in controlling gadget use and strengthening children’s literacy motivation in the digital era.